2016
DOI: 10.1007/s12374-016-0459-8
|View full text |Cite
|
Sign up to set email alerts
|

A rice White-stripe leaf3 (wsl3) mutant lacking an HD domain-containing protein affects chlorophyll biosynthesis and chloroplast development

Abstract: Leaf-color mutants are ideal genetic materials for understanding the mechanism of chloroplast development and chlorophyll (Chl) biosynthesis. Here we isolated and identified a new leaf-color mutant of rice, named whitestripe leaf3 (wsl3), from a 60 Co-irradiated mutant pool. The wsl3 mutant displayed a visible white-stripe leaf in both young seedlings and flag leaves of mature plant. Chl content in homozygous wsl3 mutant was approximately 47% of that in the wild type. Besides, chloroplast development in the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…CHLH is crucial for the Mg-chelatase activity as a catalytic subunit [ 19 ]. It has been reported that mutation of the CHLH gene leads to defective Chl and the chlorina or yellow phenotype in rice [ 8 ] and Arabidopsis thaliana [ 20 ]. Our analysis of seven intermediate products involved in Chl biosynthesis showed that the level of the substrate for Mg-chelatase increased significantly in Y plants whereas the level of the product from Mg-chelatase decreased significantly ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHLH is crucial for the Mg-chelatase activity as a catalytic subunit [ 19 ]. It has been reported that mutation of the CHLH gene leads to defective Chl and the chlorina or yellow phenotype in rice [ 8 ] and Arabidopsis thaliana [ 20 ]. Our analysis of seven intermediate products involved in Chl biosynthesis showed that the level of the substrate for Mg-chelatase increased significantly in Y plants whereas the level of the product from Mg-chelatase decreased significantly ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in any of these genes may lead to variations in the Chl contents [ 4 ], abnormal chloroplast development [ 5 ], and decreased photosynthetic efficiency [ 6 ], thereby yielding leaf color mutants. Mutants deficient in Chl biosynthesis have been identified in many higher plants, such as rice [ 7 , 8 ], Brassica napus [ 9 ], Arabidopsis thaliana [ 10 ], barley [ 11 ], and Camellia sinensis [ 12 ]. Many of the reported chlorotic mutants exhibit reduced Chl biosynthesis due to the lower activity of magnesium chelatase (Mg-chelatase) [ 11 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al established T-DNA pools for rice mutants, and 189 lines showed a chlorophyll-deficient phenotype that segregated as a single recessive locus in the T 2 generation[ 7 ]. Zhao et al identified that HD domain-containing proteins affect chlorophyll biosynthesis and chloroplast development in the white stripe leaf3 mutant [ 8 ]. Zhang et al identified an incompletely dominant gene located on chromosome 2BS flanked by the simple sequence repeat marker Xwmc25 responsible for yellow leaf color [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a lot of work has been done on the mechanism of leaf color variation. It is generally believed that the block of chloroplast development and Chl synthesis or degradation pathways in plant leaves lead to changes in leaf color (Zhao et al 2016). It was reported that a rice (Oryza sativa) leaf color mutant (ygl1) exhibited a yellow-green leaf phenotype due to a decrease of Chl synthase (Wu et al 2007).…”
Section: Introductionmentioning
confidence: 99%